Microstructural evolution of a modified HP alloy: experimental and complementary computational study (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In this work is presented results of the microstructural characterization of austenitic stainless steel (HP series) modified with Nb, aged at temperatures of 750, 800, 850, 900 and 950oC in air at different times. Microstructural changes were analyzed using optical microscopy, scanning electron microscopy (SEM) equipped with (EDS), x-ray diffraction and Vickers hardness. In the as-cast condition, the microstructure consists of an austenitic matrix and eutectic carbides network, Cr, Nb-rich carbides. The Cr-rich carbides are M7C3 type, whereas, those rich in Nb are NbC. During aging, there is a second precipitation in the matrix of very fine needle form of M23C6 carbides, which leads to an increase in hardness. After that, the decreasing in hardness is associated with a coalescence phenomenon of the secondary precipitates. Computational modeling shows that M23C6 is lesser stable than M7C3 carbide.